Pentingnya Memahami Ragam Karakteristik Peserta Didik dalam Proses Pembelajaran - Nisrina Alifah; Muhammad Solihin Rokan; Rojatul Aini; Reza Fauzi; Atika Asna (Student Research Journal, 2025)
Understanding the uniqueness of each student is one of the many tasks that teachers must do when teaching. Smart teachers must be able to identify and understand the characteristics of their students. The teaching and learning process runs more smoothly when teachers are aware of and understand the diversity of students' personalities. Children differ from one another in terms of their characteristics. Ethnicity, culture, social status, interests, cognitive development, early skills, learning styles, motivation, emotional development, social development, moral and spiritual development, and motor development are some of the many characteristics of students. In order for what they do with children to truly benefit their own lives and the lives of others, teachers are encouraged to continue to pray, be open to new ideas, and act actively and creatively towards progress in education.